Nanotechnology for telecommunications - Anwar, Sohail (Boca Raton : CRC Press, 2010)
This book provides technical information and research ideas regarding the use of nanotechnology in telecommunications and information processing, reflecting the continuing trend toward the use of optoelectronics. Nanotech will eventually lead to a technology cluster that offers a complete range of functionalities for systems used in domains including information, energy, construction, environmental, and biomedical. Describing current and future developments that hold promise for significant innovations in telecommunications.
An Overview of Nanotechnology and Nanoscience, Ahmed S. Khan -- Impact of Nanotechnology on Telecommunications, F.M. Salinas, E.F. Barros, W. Eisenberg, D.M. Smith, and S. Viswanathan -- Nanotechnology in Fiber-Optic Telecommunications: Power-Control Applications, A. Girard and M. Oron -- Nanotubes and Their Applications in Telecommunications, M. Shibli -- Silicon Nanostructures for Optical Communications, A.A. Filios, Y.S. Ryu, K. Shahrabi, and R. Tsu -- Nanostructured Optoelectronic Materials for Short-Wavelength Devices, M. Khizar and M. Yasin Akhtar Raja -- Nanophotonics for Emerging Optical Networks, K. Acharya and M.Y. Akhtar Raja -- Crystalline Colloidal Array Photonic Crystal Optical Switching, M.K. Maurer -- Processing of MEMS and NEMS, S. Allameh -- System-Level Modeling of Nano-Electromechanical Systems, K. Virk -- MEMS-Based Wireless Communications, S. Qazi -- Quantum Dot Cellular Automata: The Prospective Technology for Digital Telecommunication Systems, S.M. Nejad and E. Rahimi -- High-Electric-Field-Initiated Information Processing in Nanoelectronic Devices, V.K. Arora -- Packaging and Assembly of Microelectronic Devices and Systems, S. Manian Ramkumar -- An Architectural Perspective on Digital Quantum Switching, I. Tsai and S. Kuo -- Powering the Future with Nanotechnology, H. Efstathiadis -- Commercialization of Nanotechnology: Opportunities and Issues, S. Anwar.
Includes bibliographical references and index.
1
Keywords: Telecommunication -- Equipment and supplies; Telecommunication -- Technological innovations; Nanotechnology; Nanoelectronics